Analysis of Evidence Oath Breaker (Decesoir) in Inheritance Land Dispute - Hapsari, Diniar; Pierre Briyan Govantoro (Universitas Duta Bangsa Surakarta, 2022)
In civil law, there is evidence as stated in Article 1866 KUHPer, which includes letters, witnesses, allegations, confessions, and oaths. If there is no evidence, one of the parties may ask the panel of judges to administer an oath to the opposing party. The problems in this study are how the procedure of oath breaker in inheritance land disputes, whether the legal consequences of oath breaker if the requested oath is not true, and the strength of evidence for oath breaker in inheritance land disputes. This journal's research method uses a normative juridical approach, which emphasizes library data. The data obtained was further analyzed qualitatively. Based on the research, the breaking oath is an oath that is charged at the request of one of the parties to the opponent, which is done if there is no evidence. The legal consequences of breaking oaths are that when the actions requested by the oath are not true, the truth of the events requested by the oath becomes certain according to the law. The power of proof of the oath breaker is to decide the case which has the value of perfect, binding and decisive proof.